2018
DOI: 10.4491/eer.2018.023
|View full text |Cite
|
Sign up to set email alerts
|

The roles of polyethersulfone and polyethylene glycol additive on nanofiltration of dyes and membrane morphologies

Abstract: In this study, the effects of polymer concentration and additive in the formation of asymmetric nanofiltration (NF) membrane were evaluated. The membrane fabrication was carried out via dry/wet phase inversion technique. A new formulation of dope solution with polymer concentration ranging between 17 wt% to 21 wt% and the present of additive was developed. The results show that the permeate flux gradually decreases as polymer concentration increased, until 2.5969 L/m²h and increased the rejection up to 98.7%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…The researchers reported that the addition of polymer additive PEG which is sufficient to drive the composition of dope solution to be closed to the precipitation point (cloud point). With increasing of polymer additive concentration, the coagulant tolerance is lowered due to the highly entangled solution conformation thus resulted in a decreased of flux [60]. By adding the additive, the polymer solution became unstable and the solvents located between the polymers chains can be easily diffused out to the coagulation bath.…”
Section: Effect Of Pvp On Performances and Separation Characteristicsmentioning
confidence: 99%
“…The researchers reported that the addition of polymer additive PEG which is sufficient to drive the composition of dope solution to be closed to the precipitation point (cloud point). With increasing of polymer additive concentration, the coagulant tolerance is lowered due to the highly entangled solution conformation thus resulted in a decreased of flux [60]. By adding the additive, the polymer solution became unstable and the solvents located between the polymers chains can be easily diffused out to the coagulation bath.…”
Section: Effect Of Pvp On Performances and Separation Characteristicsmentioning
confidence: 99%
“…The produced porous membrane structures can either symmetric (isotropic) or asymmetric (anisotropic) membrane as reported by Ladewig and Al-Shaeli [11] and Gallucci et al [15]. The asymmetric membrane consists of a thin layer (skin) and porous substrate layer whereby the skin layer plays an important part as a selective barrier layer and provides major resistance to the feed solution [12,16]. The polymer solutions undergo solidification proses after being immersed in a water bath (liquid-liquid de-mixing) [17].…”
Section: Introductionmentioning
confidence: 92%
“…3 (b) shows the effect of Triton X-100 concentration on seawater flux and salt rejection of LPRO membrane. Variation of concentration plays an important role in determining the performance of the membrane [20]. The seawater flux decreases drastically as Triton X-100 was added to the casting solution which is from 6.14 L/m 2 × h to 2.69 L/m 2 × h , and then it increases up to 6.1 L/m 2 × h at 3 wt%.…”
Section: Non-ionic Surfactantmentioning
confidence: 99%